Ibn Zuhr on diseases and treatments - Packeer Mohamed, Vasila; Shuriye, Abdi Omar (IIUM Press, 2011)
This chapter investigates the contributions of Ibn Zuhr on diseases and treatments. The methodology adopted in this chapter is library based and data is collected from reliable sources. The main focus of the chapter is to provide answers on the causes and effects of disease and the treatments involved. The research explores the famous work of Ibn Zuhr namely Kitab AI-Taysir which is a medical encyclopedia